A Pilot Study to Assess the Effect of Coaching on Emergency Nurses' Stress Management - Rabia Chahbounia; Abdellah Gantare (MDPI AG, 2023)
(1) Background: Emergency nurses are more exposed to a wider range of stressors, resulting in higher levels of burnout, reducing the quality of nursing care, and decreasing job satisfaction compared with other peers in other nursing departments. The objective of the current pilot research is to evaluate the efficiency of a transtheoretical coaching model on emergency nurses' occupational stress management through a coaching intervention. (2) Materials and Methods: An interview, Karasek's stress questionnaire, the Maslach Burnout Inventory (MBI), an observation grid, and a one-group Pre-test-Post-test questionnaire was carried out to evaluate the changes in emergency nurses' knowledge and their ability to manage stress before and after attending the coaching intervention. A total of seven emergency room nurses at the proximity public hospital of the Settat area in Morocco have taken part in this study. (3) Results: The results have shown that all emergency nurses were subject to the job strain and iso-strain; four nurses were in moderate burnout, only one nurse was found in high burnout, and two were in low burnout. There was a significant difference between mean Pre- and Post-test scores (p = 0.016). Nurses' mean score has improved by 2.86 points after attending the four sessions coaching experience, passing from 3.71 in the Pre-test to 6.57 in the Post-test. (4) Conclusions: The coaching intervention through a transtheoretical coaching model could potentially be an efficient strategy for enhancing the nurses' knowledge and skills in stress management.